Region-specific gut microbiota and metabolite crosstalk underlie feed efficiency variation in Strongylocentrotus intermedius - Lin Cong; Yuehan Yan; Yu Guan; Jialiang Dong; Ziling Qin; Yi Zheng; Zhe Song; Tianqi Wang; Xiaotong Wang; Wenchao Yu (Aquaculture, 2027)

Dynamic optimization of retained-ditch height for turning-stage planning in inclined coal seam open-pit mines - Yu Wen; Ziling Song; Shiyang Xia; Wenfang Liu (Arabian Journal of Geosciences, 2026)

Dietary Lysophospholipids Enhance the Function of Lutein Rather than Lycopene in Pacific White Shrimp - Chaojie Zhu; Ziling Song; Zhengwei Ye; Yanjiao Zhang; Jiahao Liu; Lindong Xiao; Chenchen Bian; Qiang Ma; Yuliang Wei; Mengqing Liang; Houguo Xu (Fishes, 2026)
Our previous studies found that lipid emulsifiers can promote the absorption and deposition of liposoluble pigments in shrimp. The present study aimed to further investigate the effects of liposoluble pigments lutein (LUT) and lycopene (LYC), and their combination with lysophospholipids (LPL), on the growth performance, body coloration, and lipid composition of Pacific white shrimp Penaeusvannamei. Five diets were formulated: a control diet (Control), Control + 0.02% lutein (LUT), Control + 0.02% lycopene (LYC), LUT + 0.1% LPL (LUT + LPL), and LYC + 0.1% LPL (LYC + LPL). The feeding trial lasted for 8 weeks. There were no significant differences in shrimp growth and body composition among all groups. Both LUT and LYC increased the redness (a*) and yellowness (b*) of cooked shrimp. LPL synergistically enhanced the pigmentation-improving effects of LUT but weakened those of LYC. Additionally, LYC decreased the redness and yellowness of raw shrimp. Both LUT and LYC reduced the contents of saturated fatty acids and EPA while increasing the DHA content; LPL further enhanced this modulatory effect. In conclusion, LPL acts synergistically with LUT to improve the body coloration and modify the fatty acid composition of Pacific white shrimp, but its effect with LYC is limited.

The involvement of caspase-8-3 in cleavaging caspase-3 and immune response of oyster Crassostrea gigas - Chuanyan Yang; Jiachao Xu; Ziling Tong; Xiudan Wang; Shuai Jiang; Bin Yang; Lingling Wang; Linsheng Song (Fish & Shellfish Immunology, 2025)

PhenoBee: Drone-based robot for advanced field in vivo contact-based phenotyping in agriculture - Ziling Chen; Xuan Li; Tianzhang Zhao; Xing Wei; Zhihang Song; Jialei Wang; Jin Jian (Computers and Electronics in Agriculture, 2025)

Preparation of a vegetable-oil film-type emulsion dust suppressant and adsorption performance study on road dust surface in open-pit coal mines - Shiyang Xia; Ziling Song; Xiaoliang Zhao; Zhen Gao; Yu Wen; Yanning Li (Environmental Research, 2025)

A high-precision spatial and spectral imaging solution for accurate corn nitrogen content level prediction at early vegetative growth stages - Jinnuo Zhang; Xing Wei; Zhihang Song; Ziling Chen; Jian Jin (Computers and Electronics in Agriculture, 2025)

CpAGL18 is involved in the cross-talk of ethylene and auxin signaling in the regulation of fruit ripening in papaya - Jiahui Cai; Ziling Wu; Wang Zheng; Qiunan Zhu; Zunyang Song; Weixin Chen; Xueping Li; Xiaoyang Zhu (Postharvest Biology and Technology, 2025)

Spatial-spectral feature mining in hyperspectral corn leaf venation structure and its application in nitrogen content estimation - Zhihang Song; Xing Wei; Jinnuo Zhang; Ziling Chen; Jian Jin (Computers and Electronics in Agriculture, 2024)

CpAGL18 is involved in the cross-talk of ethylene and auxin signaling in the regulation of fruit ripening in papaya - Jiahui Cai; Ziling Wu; Wang Zheng; Qiunan Zhu; Zunyang Song; Weixin Chen; Xueping Li; Xiaoyang Zhu (Postharvest Biology and Technology, 2024)

Review of the recent advances in the prevention, treatment, and resource recovery of acid mine wastewater discharged in coal mines - Shiyang Xia; Ziling Song; Xiaoliang Zhao; Jiyang Li (Journal of Water Process Engineering, 2023)

Dust transport law and dust suppression technology based on gas-solid two-phase flow - Zhengzhao Jia; Ziling Song; Xiaoliang Zhao; Junfu Fan; Juyu Jiang; Xiaohe Wang (Arabian Journal of Geosciences, 2021)